Biased Affective Forecasting: A Potential Mechanism That Enhances Resilience and Well-Being - Colombo, Desirée; Fernández-Álvarez, Javier; Suso-Ribera, Carlos; Cipresso, Pietro; García-Palacios, Azucena; Riva, Giuseppe; Botella, Cristina (Frontiers in Psychology, 2020)
According to a growing body of studies, people’s ability to forecast future emotional experiences is generally biased. Nonetheless, the existing literature has mainly explored affective forecasting in relation to specific events, whereas little is still known about the ability to make general estimations of future emotional states. Based on existing evidence suggesting future-oriented disposition as a key factor for mental health, the aims of the current study were (1) to investigate the relationship between negative (NA) and positive (PA) affective forecasting biases and perceived psychological well-being, and (2) to explore whether positively biased predictions are associated with resilience and foster one’s skills to cope with stressful events. To do so, we asked 85 undergraduate students to forecast PA and NA over two weeks, as well as to report their daily affect through a web-based Ecological Momentary Assessment. According to the results, positively biased PA forecasting (i.e., overestimating positive emotional states) was associated with greater perceived psychological well-being and higher resilience. When high levels of stress were experienced, participants holding an optimistic, yet biased, estimation of future PA were more likely to successfully manage stressors, thus maintaining lower levels of NA and higher levels of positive emotions. We suggest that positively biased PA forecasting is an adaptive cognitive distortion that boosts people’s resilience and mental health, thus opening new avenues for the promotion of psychological well-being.